The Dynamics of Public Management Reform: The Transition from New Public Management to New Public Governance in a Comparative Perspective - Mohamad Kusnaeni; Harry Nenobais; Andri Micho (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Public management reform has evolved substantially over the past three decades; however, existing studies have predominantly examined New Public Management (NPM) and New Public Governance (NPG) as distinct paradigms, offering limited insight into how contemporary reforms integrate both approaches across diverse administrative contexts. This study aimed to analyze the evolution of public management reform by examining the transition from NPM to NPG and identifying the institutional factors shaping contemporary governance reform from a comparative perspective. A qualitative approach was employed through a systematic literature review and comparative analysis of scholarly publications, complemented by the foundational works of Pollitt and Bouckaert. The analysis encompassed 12 countries and the European Commission as comparative units and applied thematic content analysis to synthesize recurring reform patterns. The findings demonstrate that contemporary public management reform does not represent a linear paradigm shift from NPM to NPG. Rather, reform proceeds through institutional adaptation, whereby managerial principles remain embedded within increasingly collaborative governance arrangements. Administrative traditions, fiscal pressures, institutional capacity, digital transformation, and inter-stakeholder relationships emerged as the principal factors shaping this adaptive process. These findings extend the public management reform literature by demonstrating that governance transformation is driven by the integration of managerial and collaborative principles rather than the complete replacement of one paradigm by another. The study concludes that contemporary reform requires context-sensitive institutional adaptation that balances managerial efficiency with collaboration and public value creation. It contributes a comparative analytical framework for understanding governance transformation and offers practical implications for policymakers seeking to strengthen governance capacity through institutional coordination, digital transformation, and inter-stakeholder collaboration.